PANGERAN PARA PENGKHOTBAH: PATRON CHARLES HADDON SPURGEON DALAM KHOTBAH EKSPOSITORI BAGI GEREJA POSTMODERN - Apin Militia Christi (Diegesis : Jurnal Teologi, 2024)
Charles Haddon Spurgeon, known as the "Prince of Preachers," provides an extraordinary model for postmodern preachers through his profound and detailed expository sermons. Spurgeon emphasized the importance of exegetical accuracy, practical application, and effective rhetoric in conveying the message of the Bible. Additionally, his involvement in social work and dedication to theological education, such as the founding of The Pastor's College, demonstrate his commitment to addressing social needs and supporting the church's growth. Spurgeon's integrity and personal commitment to his ministry also serve as essential pillars for contemporary preachers to follow. Through the contextualization of the Gospel, Spurgeon successfully connected the message of the Bible with the realities of his congregation's lives, offering a relevant example for addressing the challenges of the times. Postmodern preachers are advised to adopt Spurgeon's methods and principles of ministry, including in-depth exegetical study, active involvement in social work, and continuous theological education. In doing so, preachers can deliver impactful services, strengthen the foundation of faith, and expand the church's influence within society.